2020
DOI: 10.1108/md-09-2018-1055
|View full text |Cite
|
Sign up to set email alerts
|

The effect of novelty on travel intention: the mediating effect of brand equity and travel motivation

Abstract: PurposeResearch on the relationship between novelty and travel intention is lacking. This study attempts to fill this gap by developing a theoretical model to explain how novelty influences travel intention through two mediating paths: brand equity and tourist motivation.Design/methodology/approachIn this study, data were collected from 466 foreign visitors to Taiwanese night markets. To test the model, the authors applied structural equation modeling (SEM) to identify the critical attributes that predicted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 68 publications
2
27
0
1
Order By: Relevance
“…Destination brand equity has a critical role for the destination selection process and learning how to encourage the tourists to visit specific areas is highly essential for the tourism industry. Within this context, in recent years, tourism scientists have become more aware of the importance of destination branding and an increasing number of tourism researchers have adopted the brand equity theory in their studies (Dedeoğlu, Niekerk, Weinland & Celuch 2019; Zhang et al, 2020;Rahman et al, 2021;Uslu & Ergün, 2021). This study investigates the relational link between the effect of destination brand equity dimensions on travel intention and the moderator role of nationality by means of the application of structural equation model.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Destination brand equity has a critical role for the destination selection process and learning how to encourage the tourists to visit specific areas is highly essential for the tourism industry. Within this context, in recent years, tourism scientists have become more aware of the importance of destination branding and an increasing number of tourism researchers have adopted the brand equity theory in their studies (Dedeoğlu, Niekerk, Weinland & Celuch 2019; Zhang et al, 2020;Rahman et al, 2021;Uslu & Ergün, 2021). This study investigates the relational link between the effect of destination brand equity dimensions on travel intention and the moderator role of nationality by means of the application of structural equation model.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…According to the results of our study, the degree of involvement in tourism programs is associated with rural tourism imagery, familiarity, motivation, and willingness. The investigators concluded that although tourism development has become a mature industry over a long period of time [60,61], due to its competitiveness, the high similarity of tourism characteristics in neighboring countries [29], and the impact of the COVID-19 epidemic, it has become the most important trend to create a brand image, increase tourists' attention to the scenic areas, and enhance travel ideas and motivation to facilitate the achievement of travel behavior [30].…”
Section: The Relationship Between Tourism Programs Tourists and Rural Sustainable Developmentmentioning
confidence: 99%
“…Furthermore, in order to construct a better and more rigorous theoretical foundation, a review of the survey revealed that there is a wide range of studies that individually explore the issues of tourism involvement, tourism imagery, tourism motivation, and tourism intention, and there is a considerable amount of research. A considerable number of people have explored the extent of travel program involvement on travel imagery [27,28] and travel motivation on travel intention [29]. However, there are few studies on the degree of involvement in similar travel programs or online information [30].…”
Section: Introductionmentioning
confidence: 99%
“…Travel decision-making is a factor that directly affects tourists' travel intention. Travel intention can be regarded as the result of tourists' psychological decision-making process, which leads to the actual tourism behavior and transforms perceived value into actual behavior ( 42 ). Risk perception is one of the critical factors affecting the decision-making process of tourists.…”
Section: Introductionmentioning
confidence: 99%